The Fertility and its Relation with Some Demographic, Economic and Social Variables in Jordan - et. al., Noha M. Rasheed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Migration, mortality and fertility are the main three factors that affect growth of population, and fertility is considered as the head of the list. In Jordan and according to the 2007 population census, the total fertility rate was 3.6 births per woman on average, this rate took a very closed value in 2012 were it was 3.5 on average. This relatively low and simple improvement of fertility rates helped the population growth rates to be stable as 2.2% in both years. This study was based primarily on the census data for the years 2007 and 2012, where the main objective of it is to analyze the demographic and socio-economic factors, associated with fertility in Jordan.